Pengaruh Permainan Tradisional Rangku Alu terhadap Perkembangan Motorik Kasar Anak di TKIT Baitusshalihin - Putri Situmorang; Rani Puspa Juwita; Faizatul Faridy; Hijriaty Hijriaty; Andriansyah Andriansyah (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2026)
This study aims to analyze the effect of the traditional game Rangku Alu on the gross motor development of children aged 5-6 years at TKIT Baitusshalihin, Banda Aceh. The research employed a quantitative method with a quasi-experimental approach using a non-equivalent control group design. The sample was determined through purposive sampling, consisting of Class B2 as the experimental group with 23 children and Class B1 as the control group with 26 children. Data were collected using a gross motor development observation sheet and analyzed through normality testing, homogeneity testing, and paired sample t-tests. The results indicate that the traditional game Rangku Alu has a significant effect on children’s gross motor development. This is evidenced by the improvement in gross motor skills in the experimental group, with a mean difference of -5.565 and a significance value of < 0.001, while the control group showed a mean difference of -3.269 with a significance value of < 0.001. These findings suggest that the Rangku Alu game provides a greater contribution in stimulating gross motor development in early childhood.